Efektivitas Kombinasi Teknik Relaksasi Napas Dalam dan Aromaterapi Lavender pada Penurunan Nyeri Pasca Sectio Caesarea: Studi Kasus - Sembiring, Evi Christin Br; Liana; Sinuraya, Evamona Br (Jurnal Ragam Pengabdian, 2026)
Pain is a common complaint experienced by patients after a Caesarean section and can hinder early mobilization, breastfeeding, and maternal recovery. One non-pharmacological effort that can be applied in nursing care is a combination of deep breathing relaxation techniques and lavender aromatherapy. This study aims to describe nursing care for post-Caesarean section patients who were given a combination of deep breathing relaxation techniques and lavender aromatherapy to reduce pain levels. The study used a descriptive design with a case study approach in three post-Caesarean section patients experiencing acute pain in the Alkema 4 Ward of Immanuel Hospital, Bandung. Data collection was conducted through interviews using the Numeric Rating Scale (NRS), observation, and documentation studies. The intervention was given for 10–15 minutes daily for three consecutive days. The results showed that all patients experienced a gradual decrease in pain levels from a scale of 5 (moderate pain) to a scale of 2 (mild pain) on the third day. In addition, patients appeared more relaxed, their grimacing expressions decreased, and they were able to mobilize better. These findings suggest that the combination of deep breathing relaxation techniques and lavender aromatherapy has the potential to be an effective non-pharmacological intervention as an adjunct therapy in post-cesarean section pain management. This intervention can be considered as part of evidence-based nursing practice to improve patient comfort and accelerate recovery.